2013
DOI: 10.1017/s0034412513000401
|View full text |Cite
|
Sign up to set email alerts
|

Augustine, the origin of evil, and the mystery of free will

Abstract: The question of why humanity first chose to sin is an extension to the problem of evil to which the free-will defence does not easily apply. In De libero arbitrio and elsewhere Augustine argues that as an instance of evil, the fall is necessarily inexplicable. In this article, I identify the problems with this response and attempt to construct an alternative based on Peter van Inwagen's free will 'mysterianism'. I will argue that the origin of evil is inexplicable not because it is an instance of evil, but bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“… 9. Wood is referring primarily to Katherin Rogers (2008), 104, 106. He also references similar passages written by Visser & Williams (2009), 189–191; Timpe (2012), 203; Willows (2014), 267. …”
Section: Notesmentioning
confidence: 80%
See 1 more Smart Citation
“… 9. Wood is referring primarily to Katherin Rogers (2008), 104, 106. He also references similar passages written by Visser & Williams (2009), 189–191; Timpe (2012), 203; Willows (2014), 267. …”
Section: Notesmentioning
confidence: 80%
“… 1. Among those Wood criticizes for having committed this fault are Rogers (2008); Timpe (2012); Willows (2014); Visser & Williams (2009); MacDonald (1999). …”
Section: Notesmentioning
confidence: 99%
“…Since he also desired the gift of perseverance, he could have preferred, and chosen, that good instead. It is a mystery that he preferred the former and not the latter, but once we have shown that Satan's choice is logically possible, our work is done (see also Visser and Williams (2009), 189–191; Timpe (2012), 203; Willows (2014), 267).…”
Section: Anselm Solves the Hard Problemmentioning
confidence: 99%
“…and its own effect’ ( De casu 27). Contemporary interpreters are inclined to agree with Anselm, and to treat Satan's sinful choice as no more or less mysterious than any other act of libertarian free will (see, for example: Rogers (2008), 97–107; Timpe (2012); Willows (2014)). On this line of argument, once we have shown that Satan's choice is free, and expresses his genuine preferences and desires, then no further explanations are available, even in principle.…”
Section: Anselm Solves the Hard Problemmentioning
confidence: 99%
See 1 more Smart Citation